(3efGbdI Hjf GdMcje CQSJWGdjS hGdeJfHis ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3bGd GdMcje CQSJWGdjS EPG cGfJ GdTghI ahb GdbOQg cGf gdGc GdLSe s
(3BNQgG (B:s
(3hZGjI GdeaQW ai Sdeg caGjI GdeaQW ai MO dg JeJ GdefbGdg dg Hjf GdMcje CQSJWGdjS hCHi GdWjH GdeJfHi GdTGYi Ydi jO eGdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs